Post-drought leads to increasing metabolic rates in the surface waters of a natural tropical lake - Brighenti, Ludmila Silva; Viana, Elisa Aguiar Porto; Pujoni, Diego Guimarães Florêncio; Barbosa, Francisco Antônio Rodrigues; Bezerra-Neto, José Fernandes (Frontiers in Geochemistry, 2024)
As hotspots of the global carbon cycle, lakes can regulate climate change while being regulated by it via a feedback loop. As ecosystem metabolism is considered to be a sentinel to these changes, we used high-frequency measurements and the inverse modeling approach to study the temporal dynamic of gross primary production (GPP), respiration (R), and net ecosystem production (NEP) at surface waters of a tropical lake, which lost about 60% of its volume in almost ten years. This water loss and the return of the average rainfall led to an increased concentration of nitrogen, phosphorus, and dissolved organic carbon and decreased water transparency and light availability. During the post-drought period, epilimnetic GPP increased by 40% compared with the pre-drought period, and R surpassed GPP during the mixing period of the lake. We discuss that this modification results from higher carbon and nutrient concentrations, lower light availability, and a change in the lake stratification pattern. Surface water metabolism changed due to meteorological and hydrological drought, and it may continue to change under the ongoing variation in rainfall patterns, temperature, and human disturbances.